The Effect of Porosity on Thermal Conductivity of Silicon Carbide Filled Polyproplyene Composite - Azlin Fazlina, Osman (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.